Scatter : New Scottish Art. - Third Eye Centre, Glasgow (Glasgow : Third Eye Center, 1989)
Mc Murdo, Wendy ; Fisher, Gareth ; Taylor, Linda ; Innes, Callum ; Henderson, Kevin ; Todd, Graeme ; Scullion, Louise
Scatter : New Scottish Art, Third Eye Center, Glasgow, 15 july - 27 august 1989
boek